PENGGUNAAN KIALO EDU UNTUK MENGEMBANGKAN IDE MENULIS ESAI ARGUMENTATIF : PERSEPSI MAHASISWA - Eka Fajar Rahmani (Jurnal Cakrawala Ilmiah, 2023)
This study aims to explore students' perceptions of the use of Kialo Edu in developing ideas for writing argumentative essays. The participants of this study were thirteen of sixth semester students of the Pontianak Foreign Language Institute who enrolled essay writing class. The methodology employed was a descriptive study with a three-scale closed questionnaire and semi-structured interviews as data collection instruments. The findings indicated that after using Kialo Edu for three times, students showed positive perceptions in developing ideas for writing argumentative essays. 5 of the 7 statements on the questionnaire received a 100% "agree" response. The positive response from the interview also supports this result. Referring to this result, the answer to the question has been found that the students' perception of the use of Kialo Edu is positive in helping them develop ideas for writing argumentative essays. In the other words Kialo Edu can be recommended as a platform that can be used in the classroom to develop ideas on essays that require argument elaboration, such as argumentative essays.